Genetic diversity of inbred lines in chilli based on phenotypic and genotypic responses against Colletotrichum truncatum - Herath, Herath Mudiyanselage Shalika Nadeeshani; Rafii, Mohd Yusop; Ismail, Siti Izera; Jaafar, Juju Nakasha; Ramlee, Shairul Izan (Taylor and Francis, 2022)
Anthracnose disease in chilli is one of the major problems that has been faced by farmers worldwide. This problem is further aggravated due to the lack of resistant genotypes against Colletotrichum species. It is very important to identify genotypes with resistance genes. Thirty-two inbred lines were challenged with Colletotrichum truncatum using the fruit inoculation method. Genotypic response of four resistant and three susceptible inbred lines against C. truncatum were studied using 14 SSR and two STS markers linked to disease resistance. Four inbred lines, MICH PL CA 2018/3, MICH PL CA 2018/20, MICH PL CA 2018/21 and MICH PL 35 were identified as potential disease-resistant sources against C. truncatum. Three SSR markers were selected for the validation of four resistant inbred lines and three susceptible inbred lines. Molecular markers, HpmsE 051, HpmsE 082 and HpmsE 143 were identified as potential markers to identify genotypes with resistant genes against C. truncatum.